Experimental and numerical investigation on the damping effect of net cages in waves. (May 2015) - Bi, Chun-Wei; Zhao, Yun-Peng; Dong, Guo-Hai; Cui, Yong; Gui, Fu-Kun
Abstract: A series of laboratory experiments were conducted to investigate the damping effect of net cages in waves. The wave transmission coefficient of the net cage was investigated with different wave periods, wave heights, numbers of net cages, net solidities, measurement positions, geometrical shapes of the net cage and Reynolds numbers. The experimental results show that the net cage has noticeable influence on wave propagation and the damping effect of net cages has a close relationship with many parameters. For multiple net cages, the transmission coefficient tends to increase as the wave period increases. The transmission coefficient of net cages decreases with increasing wave height. As the number of net cages increases, the wave transmission coefficient will decrease gradually. The damping effect of net cages on wave propagation tends to increase with increasing net solidity. The measurement position has an effect on the value of wave transmission coefficient. For net cages with different geometrical shapes, the circular net cage has more noticeable damping effect than the square net cage. A numerical model is introduced to simulate the interaction between waves and net cages with the fishing net treated as the porous media fluid model. The wave transmission coefficient downstream from net cages shows good agreement between experimental and numerical results. The study will contribute to understanding of the damping effect of a large fish farm on wave propagation. Highlights: Experimental and numerical studies on damping effect of net cages in waves are conducted. Influences of wave and net-cage parameters on wave propagation are analyzed. This study forms a foundation for studying the wave propagation through a fish farm.